Pengaruh Harga dan Promosi Terhadap Niat Pembelian Tiktok Shop di Kota Samarinda - Fathan Anzaini; Hudyah Astuti Sudirman; Istimaroh Istimaroh (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of price and promotion on the purchase intention of TikTok Shop users in Samarinda City. The issue addressed is the high level of user activity in browsing and liking products, which is not matched by a corresponding level of purchasing decisions. A quantitative approach was used through a survey method by distributing questionnaires to 100 active TikTok Shop users. The results show that both price and promotion have a positive and significant effect on purchase intention. Consumers are more likely to make purchases when they perceive the price as appropriate for the product quality, while attractive promotions such as discounts, vouchers, and creative content help create positive perceptions and encourage buying decisions. These findings provide valuable implications for digital business actors to design competitive pricing strategies and relevant promotional efforts to increase consumer purchase intention. Theoretically, the study reinforces that classic marketing mix elements remain relevant and influential in shaping consumer behavior in the digital era, particularly in the context of e-commerce platforms like TikTok Shop.